(untitled) (Research, Society and Development, 2020)
The present study stresses the possibility of developing complex looks, postures and actions in the midst of schooling instances - especially with regard to the exercise of teaching. It carries out a qualitative bibliographic review (André, 2013), where the thought of Edgar Morin’s Theory of Complexity (2000, 2005, 2014, 2015) is highlighted, as well as the studies of schooling in Corrêa (2006), Corrêa and Preve (2011) and Rigue (2017, 2020). It results from the research effort the understanding that the guarantees of schooling (De la fare & Corrêa, 2015), which are around the way the school institution works, hinder the development of a complex look and posture that could potentially enhance the understanding of more meaningful learning in terms of student training. Therefore, it is a great challenge to implement premises and broader understandings of Complexity Theory in school environments, when it comes to school education in Brazil.